1987
DOI: 10.1007/bf03015330
|View full text |Cite
|
Sign up to set email alerts
|

Systemic haemodynamic and metabolic effects of deliberate hypotension with isoflurane anaesthesia or sodium nitroprusside during total hip arthroplasty

Abstract: (/Oz and Qs/Qt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Ademais, FC elevada é um sinal de compensação quando existe hipotensão, o que foi observado quando a concentração anestésica esteve mais alta (2,0% e 1,8%, principalmente) (HAMLIN, 1999). Essa diminuição da pressão arterial é um efeito esperado em anestesia com isofluorano (BERNARD et al, 1987) e, por mais que tenha ocorrido alteração reflexa da FC, não houve significância clínica, pois os valores encontrados estiveram dentro de limites aceitáveis (OLIVA & FANTONI, 2010).…”
Section: Resultsunclassified
“…Ademais, FC elevada é um sinal de compensação quando existe hipotensão, o que foi observado quando a concentração anestésica esteve mais alta (2,0% e 1,8%, principalmente) (HAMLIN, 1999). Essa diminuição da pressão arterial é um efeito esperado em anestesia com isofluorano (BERNARD et al, 1987) e, por mais que tenha ocorrido alteração reflexa da FC, não houve significância clínica, pois os valores encontrados estiveram dentro de limites aceitáveis (OLIVA & FANTONI, 2010).…”
Section: Resultsunclassified
“…Anaesthetic drugs and positive pressure ventilation may have relevantly influenced LV cavity dimensions in the TOE study population by affecting systemic vascular resistance, venous tone and venous return (30). The physiologic effects of general anaesthesia and positive pressure ventilation on LV cavity size were recently demonstrated in a magnetic resonance imaging study in healthy adults (10) and several echocardiographic studies in healthy subjects and in patients with cardiac disease (9,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 98%
“…The use of SNP did not affect the results of postoperative tests of cerebral, hepatic, or renal function and myocardial status in total hip arthroplasty [34]. SNP-induced hypotension produced increases in cardiac output, oxygen consumption, and intrapulmonary shunt during total hip arthroplasty [42]. In regard to renal function, Behnia et al [43] reported that renal medullary tissue oxygenation might remain adequate in spite of a significant decrease in endogenous creatinine clearance during the SNP-induced hypotensive period.…”
Section: Effect On Hemodynamics and Organ Functionmentioning
confidence: 99%